Let's solve the equation step by step.
Given the equation: \[ 2(x - 3) + 21 = -3 \]
Step 1: Distribute to get Response area We will distribute the \(2\) in the left-hand side: \[ 2 \cdot x - 2 \cdot 3 + 21 = -3 \] This simplifies to: \[ 2x - 6 + 21 = -3 \]
Response area: \(2x - 6 + 21 = -3\)
Step 2: Combine like terms to get Response area Now, we combine the like terms \(-6\) and \(21\): \[ 2x + 15 = -3 \]
Response area: \(2x + 15 = -3\)
Step 3: Use the (choose a property) Response area to get (resulting equation) Response area Next, we will use the Subtraction Property to isolate \(2x\) by subtracting \(15\) from both sides: \[ 2x + 15 - 15 = -3 - 15 \] This simplifies to: \[ 2x = -18 \]
Response area: \(2x = -18\)
Step 4: Use the (choose a property) Response area to get (resulting answer) Response area Now, we will use the Division Property to solve for \(x\) by dividing both sides by \(2\): \[ x = \frac{-18}{2} \] This simplifies to: \[ x = -9 \]
Response area: \(x = -9\)
So, the final answer is \( x = -9 \).